Chikungunya virus infection in developing countries - What should we do? - Rahman, Md. Tanvir (Journal of Advanced Veterinary and Animal Research, 2017)
Chikungunya fever, a serious global public health problem, is a mosquito-borne disease caused by Chikungunya virus belonging to the family Togaviridae. The virus was first detected in Tanzania in1953. At present, the virus has been detected over 60 countries across the globe. The virus is transmitted mainly through Aedes mosquitoes. Although not fatal, the affected persons suffer a lot from high fever, severe pain and other complications. Currently there is no effective treatment or vaccine for the Chikungunya virus. The situation is severe in developing countries that lack sufficient diagnostic facilities and control measures. Adequate coordinated efforts comprising active surveillance, early detection, vector control and public awareness at local, national and international level need to be adopted in endemic areas for the effective control of Chikungunya virus infection. This mini review highlights some of the advances recently have made in our understanding of Chikungunya virus. http://doi.org/10.5455/javar.2017.d211 XML PubReader